Ceramic tile with sunken glaze effect and preparation method thereof

By applying multiple layers of glaze on the ceramic tiles and utilizing mutual repulsion and melting effects, the problems of unstable sinking effect and pollution absorption in the prior art are solved, and a more natural and more stain-proof tiles glaze is achieved.

CN114105477BActive Publication Date: 2025-04-15GUANGDONG NEWPEARL CERAMIC GRP CO LTD +4
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111602925.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-24
Publication Date
2025-04-15
Estimated Expiration
2041-12-24

AI Technical Summary

Technical Problem

The glaze surface of existing ceramic tiles made of corrosive glaze is unstable and has problems with absorbing stains, which affects the grade of ceramic tile.

Method used

The brick blank is covered with base glaze, surface glaze, printing ink and oily deep ink, and the mutual repulsion and melting effects of these components are used during the firing process to form a stable sunken glaze surface.

Benefits of technology

It achieves a more stable and natural sinking effect of the tile glaze. The glaze is matte, delicate in feel, better color effect, and better anti-fouling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114105477B_ABST
    Figure CN114105477B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic tiles, and specifically discloses a ceramic tile with a sunken glaze effect and a preparation method thereof. The preparation method comprises preparing a brick blank, applying a base glaze, applying a surface glaze, printing printing ink and an oily deep ink, applying a protective glaze, and firing. The preparation method comprises applying a base glaze for covering the base color of the brick blank, a surface glaze for further covering the brick blank, a printing ink for highlighting the texture of the ceramic tile, an oily deep ink for displacing the water-based surface glaze and the water-based protective glaze and for forming a sunken, and a protective glaze for forming an anti-fouling protective glaze on the brick blank. The preparation method is simple and highly controllable. Compared with a brick surface formed by an existing corrosion glaze, the sunken effect of the brick surface of the present application is more stable, and the sunken lines are smooth, natural, and lifelike; the glaze surface is matte, has a high degree of delicate hand feel, better coloring effect, and better anti-fouling performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic tiles, and in particular to a ceramic tile with a sunken glaze effect and a preparation method thereof. Background Art

[0002] The existing antique tiles with a sinking effect on the surface are generally achieved by screen printing a corrosive glaze containing vanadium pentoxide. During the firing process, vanadium pentoxide causes the glaze surface to sink by reducing the viscosity and surface tension of the glaze. However, the sinking effect formed by the corrosive glaze is unstable, and the sinking depth varies, making it difficult to control. In addition, there is dirt absorption at the position where the glaze surface sinks, thereby reducing the grade of the tile.

[0003] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a ceramic tile with a sunken glaze effect and a preparation method thereof, aiming to solve the problem that the sunken effect of the existing glaze made by etching glaze is unstable and there is the problem of dirt absorption.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a tile with a sunken glaze effect comprises the following steps:

[0007] Step 01. Prepare bricks;

[0008] Step 02. Apply base glaze on the surface of the brick;

[0009] Step 03. Apply top glaze on the surface of the base glaze;

[0010] Step 04. Printing printing ink and oily deep ink that repels the glaze on the surface of the glaze;

[0011] Step 05. Applying a protective glaze that repels the oily deep ink;

[0012] Step 06. Firing and forming.

[0013] The method for preparing tiles with a sunken glaze effect, wherein, calculated by weight, the oily deep-engraving ink comprises the following components: 37-42 parts of glaze powder, 50-54 parts of organic solvent, 3-8 parts of super dispersant, 0.5-1 part of defoaming agent and 2-3 parts of anti-settling agent; calculated by mass percentage, the chemical composition of the glaze powder is: 62%-64.5% SiO2, 4%-5.5% Al2O3, 1%-1.5% MgO, 14%-16% CaO, 0.2%-0.4% Na2O, 3.5%-4.5% K2O, 11%-13% ZnO, and the remainder is loss on ignition.

[0014] The method for preparing the ceramic tile with sunken glaze effect, wherein the organic solvent comprises the following components, calculated by weight: 50 parts of isopropyl laurate and 50 parts of isooctyl cocoate.

[0015] The method for preparing the ceramic tile with the sunken glaze effect, wherein the super dispersant is a castor oil modified polymer; the defoamer is octylphenol polyoxyethylene ether; and the anti-settling agent is oily white carbon black.

[0016] The method for preparing ceramic tiles with a sunken glaze effect, wherein the surface glaze comprises the following components, calculated by mass percentage: 47% to 52% SiO2, 13% to 17% Al2O3, 1% to 2% MgO, 7% to 10% CaO, 1% to 2% Na2O, 2% to 4% K2O, 0.5% to 2% SrO, 1% to 3% ZrO2, 6% to 10% BaO and 7% to 10% ZnO.

[0017] The method for preparing a tile with a sunken glaze effect, wherein the glaze amount of the surface glaze is 350-375 g / m 2 .

[0018] The method for preparing ceramic tiles with a sunken glaze effect, wherein the protective glaze comprises the following components, calculated by mass percentage: 47% to 52% SiO2, 13% to 17% Al2O3, 1% to 2% MgO, 8% to 11% CaO, 1% to 2% Na2O, 2% to 4% K2O, 0% to 1.5% SrO, 0% to 1% ZrO2, 8% to 10% BaO and 7% to 10% ZnO.

[0019] The method for preparing the ceramic tile with sunken glaze effect, wherein the glazing amount of the protective glaze is 350-375 g / m 2 .

[0020] The method for preparing ceramic tiles with a sunken glaze effect, wherein the base glaze comprises the following components, calculated by mass percentage: 59.06% SiO2, 7.36% TiO2, 8.71% Al2O3, 2.89% MgO, 15.69% CaO, 1.12% Na2O, 2.19% K2O, 0.01% SrO, 0.14% ZrO2, 0.02% BaO and 0.05% ZnO, and the remainder is loss on ignition.

[0021] A ceramic tile with a sunken glaze effect is prepared by the method for preparing the ceramic tile with a sunken glaze effect. The ceramic tile with a sunken glaze effect comprises, from bottom to top, a brick layer, a base glaze layer, a surface glaze layer, a printing and oily deep ink layer, and a protective glaze layer.

[0022] Beneficial effects:

[0023] The present invention provides a method for preparing ceramic tiles with a sunken glaze effect, by applying a base glaze for covering the base color of the brick blank, a surface glaze for further covering the brick blank, a printing ink for highlighting the texture of the ceramic tiles, an oily deep ink for displacing the water-based surface glaze and the water-based protective glaze and forming a sunken surface, and a protective glaze for forming an anti-fouling protective glaze on the brick blank. The preparation method is simple and highly controllable.

[0024] The present invention also provides a ceramic tile prepared by the above-mentioned preparation method. Compared with the tile surface formed by the existing corrosion glaze, the sinking effect of the ceramic tile surface is more stable, and the sinking lines are smooth, natural and realistic; the glaze surface is matte, with a high degree of delicate hand feel, better coloring effect and better anti-fouling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic structural diagram of a tile with a sunken glaze effect provided by the present invention.

[0026] Figure 2 This is a schematic diagram of the brick surface effect of the ceramic tile with sunken glaze effect prepared in Example 1.

[0027] Figure 3 This is a schematic diagram of the brick surface effect of the ceramic tile with sunken glaze effect prepared in Example 2.

[0028] Figure 4 Comparison of the brick surface effects of the tiles before firing in Comparative Example 1 and Example 3 Figure 1 .

[0029] Figure 5 Comparison of the brick surface effects of the tiles before firing in Comparative Example 1 and Example 3 Figure 2 .

[0030] Explanation of the main component symbols: 1-brick layer, 2-base glaze layer, 3-top glaze layer, 4-oily deep ink layer, 5-protective glaze layer. DETAILED DESCRIPTION

[0031] The present invention provides a ceramic tile with a sunken glaze effect and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the scope of protection of the present invention.

[0032] The present invention provides a method for preparing a tile with a sunken glaze effect, comprising the following steps:

[0033] A. Preparation of brick blanks: Brick blanks are made of conventional raw materials. The raw materials are ball milled and spray granulated, and then pressed into shape by a press. The brick blanks are dried in a drying kiln to remove some of the moisture.

[0034] B. Applying base glaze: spray or pour the base glaze on the surface of the brick; calculated by mass percentage, the base glaze includes the following components: 59.06% SiO2, 7.36% TiO2, 8.71% Al2O3, 2.89% MgO, 15.69% CaO, 1.12% Na2O, 2.19% K2O, 0.01% SrO, 0.14% ZrO2, 0.02% BaO and 0.05% ZnO, and the remainder is the loss on ignition. The amount of base glaze applied is 350-375g / m 2 The base glaze contains TiO2 with good hiding power, high whiteness and brightness, which can cover the color of the brick. The content of SiO2 in the base glaze is high, and the content of Al2O3 is low, which makes its melting temperature low. It is conducive to the formation of a large amount of glass phase with the fluxing alkali metal, which penetrates into the interior of the brick, fills the surface of the brick, and paves the way for the subsequent application of the surface glaze.

[0035] C. Spray or pour the top glaze on the surface of the base glaze; the top glaze includes the following components calculated by mass percentage: 47% to 52% SiO2, 13% to 17% Al2O3, 1% to 2% MgO, 7% to 10% CaO, 1% to 2% Na2O, 2% to 4% K2O, 0.5% to 2% SrO, 1% to 3% ZrO2, 6% to 10% BaO and 7% to 10% ZnO. The top glaze also contains zirconium silicate, sodium carboxymethyl cellulose, sodium tripolyphosphate and water. Calculated by weight, the content of solid matter in the top glaze is 100 parts, zirconium silicate is 3 to 5 parts, sodium carboxymethyl cellulose is 0.1 to 0.3 parts, sodium tripolyphosphate is 0.2 to 0.5 parts, and water is 36 to 40 parts. The top glaze has a dry weight of about 47g. The solid material is placed in a ball mill, and then zirconium silicate, sodium carboxymethyl cellulose and sodium tripolyphosphate are added for ball milling, so that the components in the glaze are fully mixed and the particle size tends to be uniform.

[0036] As a suspending agent, sodium carboxymethyl cellulose has strong adhesion ability, which allows the components in the glaze to be evenly dispersed in the system; the purpose of adding zirconium silicate is to whiten the tile, maintain ink permeability, and improve the thermal stability and chemical corrosion resistance of the tile.

[0037] The glaze amount of the top glaze is 350-375 g / m 2 The above-mentioned glaze application amount plays a role in further covering the brick blank and improving the color development effect of the printing ink. However, when the glaze application amount is too much, bubbles are easily generated, which affects the appearance quality and anti-fouling performance of the glaze surface. When the glaze application amount is too little, it is not conducive to the color development of the ink.

[0038] D. Printing printing ink and oily deep-cutting ink that repels the surface glaze on the surface of the surface glaze; the oily deep-cutting ink comprises the following components by weight: 37 to 42 parts of glaze powder, 50 to 54 parts of organic solvent, 3 to 8 parts of superdispersant, 0.5 to 1 part of defoaming agent and 2 to 3 parts of anti-settling agent.

[0039] The surface glaze contains free water, so the surface glaze is water-based glaze slurry, and the oily deep-printing ink is oily. By utilizing the principle of water-oil phase repulsion in physics, the oily deep-printing ink can be printed on the surface glaze to repel the surface glaze, forming a certain degree of depression on the glaze surface before firing. Then the glaze powder of the oily deep-printing ink melts during the firing process, making the depth of the depression deeper and the width wider, and the lines and colors of the printed ink complement each other with the oily deep-printing ink, making the depression texture of the glaze surface more natural after firing, and the simulation effect of the brick surface is good. Moreover, by controlling the position of the oily deep-printing ink and the amount of ink at each position, the sinking effect can be more controllable.

[0040] Calculated by mass percentage, the chemical composition of the glaze powder is: 62% to 64.5% SiO2, 4% to 5.5% Al2O3, 1% to 1.5% MgO, 14% to 16% CaO, 0.2% to 0.4% Na2O, 3.5% to 4.5% K2O, 11% to 13% ZnO, and the remainder is the loss on ignition. The glaze powder has a high content of silicon oxide, which has good permeability, and the glossiness of the sunken part after firing is strong. Moreover, its melting temperature is low, so that the glaze powder melts at a lower firing temperature. The low content of aluminum oxide makes the firing temperature of the glaze powder lower, sodium oxide and potassium oxide have strong fluxing ability at a lower firing temperature, calcium oxide melts into calcium glass, and zinc oxide has a fluxing effect at a higher firing temperature, so that the silicon oxide that is not melted at a lower firing temperature fully generates a glass phase, thereby improving the anti-fouling performance and glossiness of the sunken part.

[0041] Calculated by weight, the organic solvent includes the following components: 50 parts of isopropyl laurate and 50 parts of isooctyl cocoate. The isopropyl laurate is a medium-low polar oily organic solvent, and the isooctyl cocoate is an oily solvent. Both isopropyl laurate and isooctyl cocoate are difficult to volatilize, non-corrosive, and can effectively exclude water-based glaze and protective glaze. The super dispersant is a castor oil modified polymer; the super dispersant is used to improve the dispersibility of each component in the deep ink, prevent its sedimentation, and improve the stability of the deep ink; and the super dispersant is oily, and is matched with the organic solvent to prepare an oily deep ink, which is conducive to repelling the water-based glaze and protective glaze. The defoamer is octylphenol polyoxyethylene ether; when preparing the deep ink, the components in the deep ink need to be stirred and mixed evenly, and a trace amount of defoamer is added to eliminate the foam generated during the stirring process and reduce the surface tension. The anti-settling agent is oily white carbon black.

[0042] E. Spray or pour a protective glaze on the surface of the oily deep ink, which is repellent to the oily deep ink; the protective glaze comprises the following components by mass percentage: 47% to 52% SiO2, 13% to 17% Al2O3, 1% to 2% MgO, 8% to 11% CaO, 1% to 2% Na2O, 2% to 4% K2O, 0% to 1.5% SrO, 0% to 1% ZrO2, 8% to 10% BaO and 7% to 10% ZnO. Similarly, the protective glaze also contains sodium carboxymethyl cellulose, sodium tripolyphosphate and water. By weight, the content of solid matter in the protective glaze is 100 parts, sodium carboxymethyl cellulose is 0.1 to 0.3 parts, sodium tripolyphosphate is 0.2 to 0.5 parts, and water is 36 to 40 parts. The dry weight of the protective glaze is about 47g.

[0043] The protective glaze is a transparent matte glaze with good permeability. Similarly, the protective glaze is a water-based glaze slurry, which repels the oily deep-engraving ink. The oily deep-engraving ink pushes away most of the protective glaze, while a small part of the protective glaze is applied on the oily deep-engraving ink, so that the depression formed by the oily deep-engraving ink is covered with a thin layer of protective glaze, so that the depression can achieve the effect of anti-fouling.

[0044] The amount of the protective glaze applied is 350-375 g / m 2 The above glazing amount makes the protective glaze layer on the brick surface moderate in thickness, good in permeability and good in anti-fouling effect. However, if the glazing amount is too much, the depression will be covered with too much protective glaze, making the depression shallower and narrower; if the glazing amount is too little, the permeability of the glaze layer will be reduced, affecting the color rendering effect of the printing ink, and the glaze layer will be thinner, the glass phase will be less, and the anti-fouling performance of the glaze surface will be reduced.

[0045] F. Place the brick in a kiln at a temperature of 1150-1170℃ and fire for 35-45 minutes. There is a certain difference between the melting temperature of the top glaze and the melting temperature of the protective glaze, and the melting temperature difference is ±50℃, which is compatible with the above firing temperature, so that the bonding force between the bottom glaze and the top glaze is enhanced, and the top glaze and the protective glaze with a similar melting temperature are melted, so that the oily deep ink will push away the watery top glaze and the watery protective glaze, so that there are only a few top glaze and protective glaze in the position of the oily deep ink, and under the above firing conditions, the brick surface presents a natural and realistic sinking effect. Too high a firing temperature will increase the fluidity of the protective glaze, and most of the protective glaze will enter the sink formed by the oily deep ink, making the depth of the sink shallower and the width narrower; while too low a firing temperature will cause the top glaze to collapse, affecting the flatness of the glaze surface; making the ceramic tile incompletely vitrified and reducing the hardness of the tile.

[0046] The preparation method is simple and highly controllable by applying a base glaze for covering the base color of the brick blank, a surface glaze for further covering the brick blank, a printing ink for highlighting the texture of the tile, an oily deep ink for displacing the water-based surface glaze and the water-based protective glaze and forming a sunken surface, and a protective glaze for forming an anti-fouling protective glaze on the brick blank. Compared with the brick surface formed by the existing corrosion glaze, the brick surface of the present application has a more stable sunken effect, a matte glaze surface, a high degree of fineness in hand feel, a better coloring effect, and better anti-fouling performance. Moreover, compared with screen printing, the present invention adopts a glazing method of spraying glaze or pouring glaze, which does not require multiple cleaning of the screen, and the screen is easily damaged during the cleaning process. The production efficiency is increased from the existing 4,500 to 5,000 square meters to 9,000 square meters, which is conducive to improving the production line speed.

[0047] See also Figure 1 The present invention also provides a ceramic tile with a sunken glaze effect, which is prepared by the method for preparing the ceramic tile with a sunken glaze effect. The ceramic tile with a sunken glaze effect comprises, from bottom to top, a brick layer 1, a bottom glaze layer 2, a surface glaze layer 3, a printing and oily deep ink layer 4, and a protective glaze layer 5.

[0048] In order to further illustrate the preparation method of a ceramic tile with a sunken glaze effect provided by the present invention, the following examples are provided.

[0049] Example 1

[0050] A method for preparing a tile with a sunken glaze effect comprises the following steps:

[0051] A. Preparation of bricks: The raw materials are ball-milled and spray-granulated, and then pressed into shape by a press. The bricks are dried in a drying kiln.

[0052] B. Applying base glaze: spray or pour the base glaze on the surface of the brick; calculated by mass percentage, the base glaze includes the following components: 59.06% SiO2, 7.36% TiO2, 8.71% Al2O3, 2.89% MgO, 15.69% CaO, 1.12% Na2O, 2.19% K2O, 0.01% SrO, 0.14% ZrO2, 0.02% BaO and 0.05% ZnO, and the remainder is the loss on ignition. The amount of base glaze applied is 360g / m 2 .

[0053] C. Spray or pour the top glaze on the surface of the base glaze; calculated by mass percentage, the top glaze includes the following components: 49.95% SiO2, 14.69% Al2O3, 1.16% MgO, 8.28% CaO, 1.71% Na2O, 3.20% K2O, 1.57% SrO, 2.27% ZrO2, 8.00% BaO, 7.50% ZnO, and the loss on ignition is 1.67%. The melting temperature of the top glaze is 1126°C, and the melting temperature coefficient is 0.374. The top glaze also contains zirconium silicate, sodium carboxymethyl cellulose, sodium tripolyphosphate and water. Calculated by weight, the content of solid matter in the top glaze is 100 parts, zirconium silicate is 3 parts, sodium carboxymethyl cellulose is 0.2 parts, sodium tripolyphosphate is 0.5 parts, and water is 38 parts. The glaze application amount of the top glaze is 375g / m 2 .

[0054] D. Printing printing ink and oily deep ink repelling the glaze on the surface of the glaze; the oily deep ink comprises the following components by weight: 37 parts of glaze powder, 52 parts of organic solvent, 8 parts of castor oil modified polymer, 0.8 parts of octylphenol polyoxyethylene ether and 2 parts of oily white carbon black. The chemical composition of the glaze powder by mass percentage is: 63.17% SiO2, 4.6% Al2O3, 1.35% MgO, 15.19% CaO, 0.32% Na2O, 4.04% K2O, 11.33% ZnO. The organic solvent comprises the following components by weight: 50 parts of isopropyl laurate and 50 parts of isooctyl cocoate.

[0055] E. Spray or pour a protective glaze on the surface of the oily deep ink that repels the oily deep ink; the protective glaze includes the following components calculated by mass percentage: 49.94% SiO2, 14.72% Al2O3, 1.16% MgO, 9.49% CaO, 1.67% Na2O, 2.89% K2O, 0.49% SrO, 0.06% ZrO2, 9.13% BaO, 8.85% ZnO, and the loss on ignition is 1.60%. The melting temperature of the protective glaze is 1086°C, and the melting temperature coefficient is 0.414. The protective glaze also contains sodium carboxymethyl cellulose, sodium tripolyphosphate and water. Calculated by weight, the content of solid matter in the protective glaze is 100 parts, sodium carboxymethyl cellulose is 0.2 parts, sodium tripolyphosphate is 0.5 parts, and water is 38 parts. The glaze application amount of the protective glaze is 350g / m 2 .

[0056] F. Place the bricks in a kiln at a temperature of 1170°C and fire for 35 minutes.

[0057] Example 2

[0058] A method for preparing a tile with a sunken glaze effect comprises the following steps:

[0059] A. Preparation of bricks: The raw materials are ball-milled and spray-granulated, and then pressed into shape by a press. The bricks are dried in a drying kiln.

[0060] B. Applying base glaze: spray or pour the base glaze on the surface of the brick; calculated by mass percentage, the base glaze includes the following components: 59.06% SiO2, 7.36% TiO2, 8.71% Al2O3, 2.89% MgO, 15.69% CaO, 1.12% Na2O, 2.19% K2O, 0.01% SrO, 0.14% ZrO2, 0.02% BaO and 0.05% ZnO, and the remainder is the loss on ignition. The amount of base glaze applied is 350g / m 2 .

[0061] C. Spray or pour the top glaze on the surface of the base glaze; calculated by mass percentage, the top glaze includes the following components: 47.33% SiO2, 16.42% Al2O3, 1.67% MgO, 9.49% CaO, 1.88% Na2O, 3.57% K2O, 1.02% SrO, 1.23% ZrO2, 6.43% BaO, 9.31% ZnO, and the loss on ignition is 1.65%. The melting temperature of the top glaze is 1142°C. The top glaze also contains zirconium silicate, sodium carboxymethyl cellulose, sodium tripolyphosphate and water. Calculated by weight, the solid matter content in the top glaze is 100 parts, zirconium silicate is 5 parts, sodium carboxymethyl cellulose is 0.1 parts, sodium tripolyphosphate is 0.2 parts, and water is 40 parts. The glaze application amount of the top glaze is 360g / m 2 .

[0062] D. Printing printing ink and oily deep ink repelling the glaze on the surface of the glaze; the oily deep ink comprises the following components by weight: 40 parts of glaze powder, 54 parts of organic solvent, 5 parts of castor oil modified polymer, 0.5 parts of octylphenol polyoxyethylene ether and 2.5 parts of oily white carbon black. The chemical composition of the glaze powder is 64.01% SiO2, 4.1% Al2O3, 1.22% MgO, 14.34% CaO, 0.25% Na2O, 3.61% K2O, 12.33% ZnO, and the remainder is the ignition loss. The organic solvent comprises the following components by weight: 50 parts of isopropyl laurate and 50 parts of isooctyl cocoate.

[0063] E. Spray or pour a protective glaze on the surface of the oily deep ink that repels the oily deep ink; calculated by mass percentage, the protective glaze includes the following components: 47.41% SiO2, 16.88% Al2O3, 1.52% MgO, 8.69% CaO, 1.42% Na2O, 2.15% K2O, 1.48% SrO, 0.2% ZrO2, 8.64% BaO, 9.71% ZnO, and the loss on ignition is 1.90%. The melting temperature of the protective glaze is 1100°C. The protective glaze also contains sodium carboxymethyl cellulose, sodium tripolyphosphate and water. Calculated by weight, the content of solid matter in the protective glaze is 100 parts, sodium carboxymethyl cellulose is 0.1 parts, sodium tripolyphosphate is 0.2 parts, and water is 40 parts. The glaze application amount of the protective glaze is 375g / m 2 .

[0064] F. Place the bricks in a kiln at a temperature of 1160°C and fire for 40 minutes.

[0065] Example 3

[0066] A method for preparing a tile with a sunken glaze effect comprises the following steps:

[0067] A. Preparation of bricks: The raw materials are ball-milled and spray-granulated, and then pressed into shape by a press. The bricks are dried in a drying kiln.

[0068] B. Applying base glaze: spray or pour the base glaze on the surface of the brick; calculated by mass percentage, the base glaze includes the following components: 59.06% SiO2, 7.36% TiO2, 8.71% Al2O3, 2.89% MgO, 15.69% CaO, 1.12% Na2O, 2.19% K2O, 0.01% SrO, 0.14% ZrO2, 0.02% BaO and 0.05% ZnO, and the remainder is the loss on ignition. The amount of base glaze applied is 375g / m 2 .

[0069] C. Spray or pour the top glaze on the surface of the base glaze; calculated by mass percentage, the top glaze includes the following components: 51.23% SiO2, 13.67% Al2O3, 1.78% MgO, 7.64% CaO, 1.49% Na2O, 2.88% K2O, 0.71% SrO, 1.72% ZrO2, 9.45% BaO, 8.28% ZnO, and the loss on ignition is 1.15%. The melting temperature of the top glaze is 1108°C. The top glaze also contains zirconium silicate, sodium carboxymethyl cellulose, sodium tripolyphosphate and water. Calculated by weight, the content of solid matter in the top glaze is 100 parts, zirconium silicate is 4 parts, sodium carboxymethyl cellulose is 0.3 parts, sodium tripolyphosphate is 0.3 parts, and water is 36 parts. The glaze application amount of the top glaze is 350g / m2 .

[0070] D. Printing printing ink and oily deep ink repelling the glaze on the surface of the glaze; the oily deep ink comprises the following components by weight: 42 parts of glaze powder, 50 parts of organic solvent, 3 parts of castor oil modified polymer, 1 part of octylphenol polyoxyethylene ether and 3 parts of oily white carbon black. The chemical composition of the glaze powder is 62.02% SiO2, 5.38% Al2O3, 1.44% MgO, 14.72% CaO, 0.38% Na2O, 4.12% K2O, 11.82% ZnO, and the remainder is the ignition loss. The organic solvent comprises the following components by weight: 50 parts of isopropyl laurate and 50 parts of isooctyl cocoate.

[0071] E. Spray or pour a protective glaze on the surface of the oily deep ink, which is repellent to the oily deep ink; the protective glaze comprises the following components by mass percentage: 51.38% SiO2, 14.23% Al2O3, 1.29% MgO, 10.01% CaO, 1.32% Na2O, 3.01% K2O, 0.71% SrO, 0.70% ZrO2, 8.72% BaO, 7.65% ZnO, and the loss on ignition is 0.98%. The melting point of the protective glaze is 1073°C. The protective glaze also contains sodium carboxymethyl cellulose, sodium tripolyphosphate and water. Calculated by weight, the content of solid matter in the protective glaze is 100 parts, sodium carboxymethyl cellulose is 0.3 parts, sodium tripolyphosphate is 0.3 parts, and water is 36 parts. The glaze application amount of the protective glaze is 360g / m 2 .

[0072] F. Place the bricks in a kiln at 1150°C and fire for 45 minutes.

[0073] Comparative Example 1

[0074] The preparation method of comparative example 1 is basically the same as that of embodiment 3, except that the formula of deep ink is different. Calculated by weight, the ink includes the following components: 35 parts of frit powder, 58 parts of organic solvent, 4 parts of castor oil modified polymer, 0.5 parts of octylphenol polyoxyethylene ether and 2.5 parts of oily white carbon black. Calculated by mass percentage, the chemical composition of the frit powder is: 47.98% SiO2, 0.11% TiO2, 22.75% Al2O3, 1.85% MgO, 10.99% CaO, 0.13% Na2O, 3.16% K2O, 4.55% BaO, 0.01% ZnO, and the remainder is the loss on ignition. Calculated by weight, the organic solvent includes the following components: 30 parts of isopropyl laurate, 40 parts of isooctyl cocoate, 15 parts of high boiling point white oil and 15 parts of acrylic resin.

[0075] Performance Testing

[0076] According to GB / T 3810.14-2006 "Test Methods for Ceramic Tiles" Part 14: Determination of Pollution Resistance, the ceramic tiles prepared in Examples 1-3 and Comparative Example 1 were tested. The test results showed that the stains on the tile surfaces of Examples 1-3 and Comparative Example 1 were wiped off, indicating that the anti-fouling grade of the ceramic tiles prepared in Examples 1-3 and Comparative Example 1 reached Grade Five.

[0077] The Mohs hardness of the tiles made in Examples 1-3 all reached level 4. The glossiness of the tiles in Examples 1-3 was 15.0°, 14.5° and 15.5°, respectively. The glossiness was moderate and had a matte tile surface effect. Visual inspection at a distance of 0.8 meters showed no difference compared with the comparison sample. The tile surface felt smooth and delicate, without any pricking sensation. Please refer to Figure 2 and Figure 3 , observing the brick surface from the side, it can be seen that the sinking effect is deep and shallow, and the sunken lines are smooth, natural and realistic.

[0078] from Figure 4 and Figure 5 It can be seen that the sinking effect of the glaze surface in Comparative Example 1 is not obvious, that is, the content of isopropyl laurate and isooctyl cocoate added in Comparative Example 1 is lower than that in Example 3, so that the oily organic solvent forms a significant difference in the displacement of the surface glaze and the protective glaze with the same glazing amount. In addition, since the protective glaze is applied on the brick surface in Comparative Example 1, the protective glaze covers a part of the formed sinking, thereby making the depth of the sinking effect shallower. ( Figure 4 and Figure 5 The brick surface in the figure is a schematic diagram of the brick surface after printing ink, oil-based ink and protective glaze. Since the protective glaze is white before firing, it becomes translucent after firing to show the printing ink. Figure 4 and Figure 5 The middle brick surface is white. Figure 4 and Figure 5 It can be seen intuitively that before the tiles were fired, the oily deep ink was printed, and the deep ink had already sunken. ) In addition, since the SiO2 content added in Example 3 is greater than that in Comparative Example 1, the sunken in Example 3 is glossy, while the sunken in Comparative Document 1 is matte.

[0079] In summary, the present invention applies a base glaze for covering the base color of the brick blank, a surface glaze for further covering the brick blank, a printing ink for highlighting the texture of the tile, an oily deep ink for displacing the water-based surface glaze and the water-based protective glaze and for forming a sunken surface, and a protective glaze for forming an anti-fouling protective glaze on the brick blank. The preparation method is simple and has high controllability. Compared with the brick surface formed by the existing corrosive glaze, the brick surface of the present application has a more stable sunken effect, and the sunken lines are smooth, natural and realistic; the glaze surface is matte, the hand feel is fine, the coloring effect is better, and the anti-fouling performance is better.

[0080] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the present invention.

Claims

1. A method for preparing a tile with a sunken glaze effect, characterized in that: The steps include: Step 01. Prepare bricks; Step 02. Apply base glaze on the surface of the brick; Step 03. Apply top glaze on the surface of the base glaze; Step 04. Printing printing ink and oily deep ink that repels the glaze on the surface of the glaze; Step 05. Applying a protective glaze that repels the oily deep ink; Step 06. Firing and molding; the firing and molding conditions are 1150-1170°C and the time is 35-45 minutes; Wherein, the oily deep ink comprises the following components, calculated by weight: 37-42 parts of glaze powder, 50-54 parts of organic solvent, 3-8 parts of super dispersant, 0.5-1 parts of defoamer and 2-3 parts of anti-settling agent; calculated by mass percentage, the chemical composition of the glaze powder is: 62%-64.5% SiO2, 4%-5.5% Al2O3, 1%-1.5% MgO, 14%-16% CaO, 0.2%-0.4% Na2O, 3.5%-4.5% K2O, 11%-13% ZnO, and the balance is loss on ignition; The organic solvent comprises the following components by weight: 50 parts of isopropyl laurate and 50 parts of isooctyl cocoate; the hyperdispersant is a castor oil modified polymer; the defoamer is octylphenol polyoxyethylene ether; the anti-settling agent is oily white carbon black; Calculated by mass percentage, the glaze includes the following components: 47% to 52% SiO2, 13% to 17% Al2O3, 1% to 2% MgO, 7% to 10% CaO, 1% to 2% Na2O, 2% to 4% K2O, 0.5% to 2% SrO, 1% to 3% ZrO2, 6% to 10% BaO and 7% to 10% ZnO; the glaze application amount of the glaze is 350 to 375 g / m 2 ; Calculated by mass percentage, the protective glaze includes the following components: 47% to 52% SiO2, 13% to 17% Al2O3, 1% to 2% MgO, 8% to 11% CaO, 1% to 2% Na2O, 2% to 4% K2O, 0% to 1.5% SrO, 0% to 1% ZrO2, 8% to 10% BaO and 7% to 10% ZnO; the glaze amount of the protective glaze is 350 to 375 g / m 2 ; Calculated by mass percentage, the base glaze includes the following components: 59.06% SiO2, 7.36% TiO2, 8.71% Al2O3, 2.89% MgO, 15.69% CaO, 1.12% Na2O, 2.19% K2O, 0.01% SrO, 0.14% ZrO2, 0.02% BaO and 0.05% ZnO, and the remainder is the loss on ignition.

2. A ceramic tile with a sunken glaze effect, characterized in that: The ceramic tile with sunken glaze effect is prepared by the preparation method of claim 1, wherein the ceramic tile with sunken glaze effect comprises, from bottom to top, a brick layer, a base glaze layer, a surface glaze layer, a printing and oily deep ink layer, and a protective glaze layer.

Citation Information

Patent Citations

  • Ceramic plate with three-dimensional fine weaving texture effect and preparation method thereof

    CN110483103A

  • Manufacturing method of ceramic chip with fine mold textures

    CN112142328A